Adult sport participation preference of elementary school students - Carr, Nancy L. (My University, 1988)
This study was designed to determine if sex, age, and family sport participation had any influence on elementary school students' (N=222, age 6-10) choices of type and number of sports to participate in upon reaching adulthood. A twenty-seven item questionnaire was used to determine age, sex, desire to participate in a given sport, as well as the number of sports chosen. [Questionnaire responses were evaluated by determining frequency and percentage of yes versus no answers to each sport.] A X2 test was used to determine statistical significance between sex, age, age by sex variables for selected sports choices (p <.05). A two-way ANOVA and a Scheffe Post Hoc test were used to analyze sex and age differences in the number of sports chosen (p <.05). It was concluded that sex, age, and age by sex variables had a significant relationship to selected sports choices. Sex showed a significant difference in the number of sports chosen. Males chose significantly more sports than females. Age showed a significant difference in that six year olds selected significantly more sports for participation than the eight year olds. No significant differences were seen in age by sex groupings and number of sports chosen.
Keywords: Sports.; School children.; Attitudes.